EFEKTIVITAS EKSTRAKDAUN BENALU NANGKA (Macrosolencochinchinensis (Lour.) van Tiegh) DALAM MENCEGAH PERTUMBUHAN TUMOR PARU MENCIT BETINA - Nurahmanto, Dwi; Meiyanto, Edy (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2013)
Cancer was ranked first as the cause of death in all over the world. Chemopreventive sought from traditional preparations for example, various types of plant parasites. This study aims to determine the chemopreventive activity of aqueous extract of leaves of parasites jackfruit ( Macrosolen cochinchinensis ( Lour. ) van Tiegh ) on the growth of lung tumors of mice ( Mus musculus ) female strain Balb / c induced benzo [a ] pyrene . This research was conducted using the method Newborn Mice. Test animals used female mice (Mus musculus) strain BALB / c and benzo [ a] pyrene as carcinogenic compounds. Female mice were divided into 5 groups. Cancer control group were injected with B [ a] P were dissolved in dimethylsulfoxide ( DMSO ) . Solvent control group was given the same volume of DMSO in the control of cancer. The treatment group was divided into three dose groups are a dose of 250, 500, and 750 mg / kg . Extract made after female mice induced B [a] P. Chemopreventive intensity expressed as percentage inhibition of tumors in each group by counting the number of tumor nodules on average per lung in each mouse organs within each group. Statistical analysis used is the analysis of Test homogenity of variances and continued with Mann- Whitney Test. Parasite jackfruit leaf aqueous extract (Macrosolencochincinensis (Lour.) van Tiegh) dose of I, II, and III were able to inhibit development into lung of female mice with the percentage inhibition respectively 50 %, 36.87 %, and 84.57 % .